Krisztinavárosi Kábeltelevízió
report by dr. György Kapin police lieutenant colonel on the district police's activities in 1994, setting up a civil guard, the catacombes of the Castle, Aerocaritas air rescue, street musicians, József Csőke film director, Olympic games, football history, weight lifting, Tokio 1964, Munich 1972 100th anniversary of Kosciouscó Tádé primary school, sports and concerts at the Academy of Music